Factors associated with food insecurity among pregnant women assisted by Universal Health Care in Lavras - Minas Gerais State - Renata Oliveira Messina Costa; Ana Poblacion; Carolina Lourenço Giudice; Lahis Cristina Morais de Moura; Adriany Aparecida Roquini Lima; Daniela Braga Lima; Maysa Helena de Aguiar Toloni; Lílian Gonçalves Teixeira (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to investigate sociodemographic and economic factors associated with food insecurity among pregnant women assisted by the universal healthcare network of Lavras, Minas Gerais. Methods: a cross-sectional study investigated socioeconomic and demographic, obstetric, and nutritional conditions experienced by pregnant women. Households in which pregnant women lived were classified as food secure or food insecure using the Brazilian Food Insecurity Scale. Prevalence estimates and prevalence ratios with 95% confidence intervals were generated to test for associations between food insecurity and several socioeconomic and demographic indicators using Poisson regression analysis. Results: among 173 pregnant women who participated in the study, 48% lived in households with some level of food insecurity. Adjusted models showed that pregnant women living in food-insecure households had higher prevalence ratios of lower education attainment (aPR = 1.43, CI95% = 1.07-1.91), woman being the head of the household (aPR = 1.39, CI95% = 1.02-1.87), having family monthly income lower than 1 ½ MW (aPR = 1.68, CI95% = 1.11-2.52) and participating in the government cash transfer program (aPR = 1.47, CI95% = 1.08-1.99). Conclusions: the high prevalence of food insecurity in pregnant women assisted by the public healthcare system was associated with structural social factors. Results of this study will contribute to develop an intersectoral health and nutrition policy in order to promote food security among marginalized communities and vulnerable populations, such as pregnant women.